Prognostic factors in aneurysmal subarachnoid hemorrhage with poor initial clinical grade - Culebras, Diego; Pedrosa, Leire; Mosteiro, Alejandra; Llull, Laura; Topczewski, Thomaz; Zattera, Luigi; Díez-Salvatierra, Laura; Dolz, Guillem; Amaro, Sergi; Torné, Ramon (Frontiers in Neurology, 2025)
IntroductionAneurysmal subarachnoid hemorrhage (aSAH) is a rare cause of stroke that poses significant morbidity and mortality, as it affects patients around the age of 50 years. While advances in early aneurysm intervention have reduced mortality rates, many patients still experience poor outcomes due to early brain injury (EBI) and delayed cerebral ischemia (DCI). This study aims to explore the characteristics of patients with poor neurological outcomes among patients with poor neurological status at admission, using comprehensive clinical and neuroimaging data.MethodsWe analyzed 377 aSAH patients (WFNS 4–5) admitted between 2013 and 2020, focusing on demographics, clinical assessments, imaging, treatments, and outcomes at discharge and 3 months later.ResultsAmong the cohort, which predominantly consisted of females, the mortality rate was 49%. Our findings indicate that older patients had poorer functional outcomes; notably, 59% of patients aged 75 and older had limitations on therapeutic efforts, leading to a 100% mortality rate in that subgroup. There was no difference in outcomes between endovascular and surgical treatments. However, patients undergoing multimodal monitoring had better functional outcomes at discharge. Angiographic vasospasm was found in 31% of patients and was linked to poorer outcomes at discharge (p = 0.016). Though DCI did not directly correlate with functional outcomes, it correlated strongly with new cerebral infarcts (90% incidence).ConclusionThe prognosis of patients with aSAH and poor neurological status on admission is generally poor. Multimodal monitoring and tailored treatment appear to be beneficial in achieving favorable results in these patients. Despite the initial severity, up to 20% of patients achieve a good functional result on discharge and up to 35% do so at 3 months. These should be considered in the initial prognostic assessment with the families of these patients.